Bacterial artificial chromosome cloning and mapping of a 630-kb human extrachromosomal structure. - Wang, M; Shouse, S; Lipes, B; Kim, U J; Shizuya, H; Lai, E

(untitled) (Genome Research, 1996)
We have cloned and mapped a circular 630-kb human extrachromosomal structure (termed amplisome) using the bacterial artificial chromosome (BAC) cloning system. Twenty-one BACs were isolated from an amplisome-enriched library by colony hybridization. The insert sizes range from 25 to 143 kb, with an average size of 82 kb. The coverage of the amplisome in clones is approximately 2.7-fold. To construct a physical map of the amplisome, we used three different but complementary methods: hybridization, STS content mapping, and fingerprinting. In addition, we compared the advantages and the drawbacks of these techniques in mapping the amplisomal BACs. The 21 BACs were grouped into two contigs and the two small gaps (3.5 and 26.5 kb) were filled by screening of a human genomic BAC library. The organization of the amplisome revealed by the BAC-based physical map is consistent with the long-range restriction map reported previously. Our results demonstrate that a 630-kb region can be rapidly cloned and mapped into contigs by use of the BAC system. Because of the low frequency (<0.1%) of chimerism and rearrangement, these BAC clones are ready for DNA sequencing and functional analysis.